A modeling framework for evaluating streambank stabilization practices for reach-scale sediment reduction. (February 2018) - Enlow, Holly K.; Fox, Garey A.; Boyer, Tracy A.; Stoecker, Art; Storm, Daniel E.; Starks, Patrick; Guertault, Lucie
Abstract: Process-based models can predict stream response to streambank stabilization. However, a framework does not exist on how to explicitly utilize these models to evaluate stabilization measures prior to implementation. This research developed a framework to evaluate stabilization practices using hydraulic and sediment transport models, landowner preferences, construction costs, and effectiveness. This framework produces sediment reduction graphs to determine the stabilization length as well as cost graphs. The methodology was applied to Fivemile Creek in western Oklahoma. A CONCEPTS simulation was developed for a 10.25-km reach and several stabilization techniques (grade control, riprap toe, and vegetation) were simulated. Incorporating multiple stabilization practices simultaneously resulted in higher sediment loads, but also higher costs which were quantifiable using the framework. Vegetation with 2:1 bank slopes was the most cost-effective stabilization technique. With that said, the framework provided a process-based understanding of the system that also highlighted the need for grade control for long-term effectiveness. Highlights: Framework for using process-based models to evaluate bank stabilization projects. Sediment reduction and cost data generated for predicting stabilization success. Framework applied to Fivemile Creek in western Oklahoma as case study. Implemented CONCEPTS model for hydraulics, sediment transport, and bank failure.